'Sometimes Uncomfortable, Sometimes Arousing': The Slow Dramaturgy of Casey Jenkins's Craftivist Performances. Issue 2 (7th June 2016) - STEVENS, LARA
Abstract : From mid-October to mid-November 2013, Australian performance artist Casey Jenkins sat for twenty-eight days in a gallery in Darwin, far North Australia, knitting a scarf from a ball of wool lodged in her vagina. Parts of the performance of Casting Off My Womb were filmed by the public broadcasting service SBS2, and aired in late November 2013 as a two-minute-and-forty-eight-second video clip re-titled Vaginal Knitting . The clip went viral on YouTube, with over seven million views as of March 2016, and received extensive media attention. Casting Off My Womb attracted global public interest because Jenkins continued to knit throughout the days of her period, weaving her menstrual blood into the artwork. The performance elicited strong responses from its global viewing public. While some people praised the work, many online spectators wrote vicious, derisive and personal attacks on Jenkins for displaying her menstrual blood in a public place. This article uses Matthew Goulish's methodology of 'slow thinking' as a counterresponse to the impulsive reactions of the online spectators and as a means to register the powerful and incremental energy and effects of Jenkins's feminist performance.